2022
DOI: 10.1111/anae.15617
|View full text |Cite
|
Sign up to set email alerts
|

Peri‐operative management of patients with Parkinson’s disease

Abstract: Patients with Parkinson's disease are at higher risk of peri-operative medical and surgical complications. Multidisciplinary management, early recognition of potential complications, specialised care of medications and intra-operative protection of the vulnerable brain are all important aspects of the peri-operative management of patients with Parkinson's disease. Advances in continuous dopaminergic treatment, development of a peri-operative Parkinson's disease pathway and application of telemedicine are start… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…This challenge of facilitating such cross-talk is not exclusive to MHT—prior work in other medical specialties has demonstrated the importance of integrating the efforts of researchers and clinicians, who frequently function independently. One example is deep brain stimulation (DBS), a technique in the rapidly evolving subfield of functional neurosurgery that integrates aspects of neurology, psychiatry, neuroscience, and electrical engineering [ 124 , 125 ]. DBS has an established organizational framework for multidisciplinary communication that enables independent regional groups of experts in the aforementioned disciplines to communicate regularly and stay abreast of recent updates [ 126 , 127 ].…”
Section: Discussionmentioning
confidence: 99%
“…This challenge of facilitating such cross-talk is not exclusive to MHT—prior work in other medical specialties has demonstrated the importance of integrating the efforts of researchers and clinicians, who frequently function independently. One example is deep brain stimulation (DBS), a technique in the rapidly evolving subfield of functional neurosurgery that integrates aspects of neurology, psychiatry, neuroscience, and electrical engineering [ 124 , 125 ]. DBS has an established organizational framework for multidisciplinary communication that enables independent regional groups of experts in the aforementioned disciplines to communicate regularly and stay abreast of recent updates [ 126 , 127 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, it was observed that the most commonly preferred drugs for sedation management were propofol and midazolam. Although propofol has been reported to trigger dyskinesia (13), it can still be used in patients with movement disorders (14) and is one of the frequently preferred agents for sedation in MR imaging units (15). The use of dexmedetomidine has been reported for preventing the dyskinesia triggered by propofol (13).…”
Section: Discussionmentioning
confidence: 99%
“…Pre-operative considerations broadly encompass system evaluation, operative scheduling, and medication scheduling (21). Patients with PD may have other associated comorbidities and poor general health; therefore, a system evaluation during the pre-operative assessment is also essential.…”
Section: Pre-operative Anaesthetic Considerationsmentioning
confidence: 99%